2004
DOI: 10.1023/b:ijtp.0000028862.91652.98
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Standard Quantum Mechanics for the Description of Compound Quantum Entities

Abstract: We reformulate the 'separated quantum entities' theorem, i.e. the theorem that proves that two separated quantum entities cannot be described by means of standard quantum mechanics, within the fully elaborated operational Geneva-Brussels approach to quantum axiomatics, where the basic mathematical structure is that of a State Property System. We give arguments that show that the core of this result indicates a failure of standard quantum mechanics, and not just some peculiar shortcoming due to the axiomatic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…For the compound system in the quantum limit tests along non orthogonal measurement directions are always compatible but not separable. Therefore, these tests and a fortiori the subsystems are not separated, which is in agreement with previous results stating that separated quantum entities cannot be described in quantum theory [1,2,4,23,24,25]. For intermediate values of the parameter we found that all tests are compatible, but they are only separable if θ u1u2 = π 2 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For the compound system in the quantum limit tests along non orthogonal measurement directions are always compatible but not separable. Therefore, these tests and a fortiori the subsystems are not separated, which is in agreement with previous results stating that separated quantum entities cannot be described in quantum theory [1,2,4,23,24,25]. For intermediate values of the parameter we found that all tests are compatible, but they are only separable if θ u1u2 = π 2 .…”
Section: Discussionsupporting
confidence: 91%
“…For the example of the connected vessels of water it is clear that the considered tests cannot be separated because of the clear physical connection between the two vessels. For entangled quantum systems we encounter non-separated tests in a natural way (actually it is not possible to describe a compound system of two separated quantum systems within the formalism of quantum theory [1,2,4,23,24,25]), but the origin of this quantum non-separability is still a matter of debate for physicists and philosophers alike. To shed more light on this issue, we discuss in the next section a macroscopic model of a compound system of two entangled spin 1/2 in the singlet state, in which tests are defined by a parameter reflecting randomness in the measurement such that we obtain a continuous transition from a quantum system to a classical system, and check what happens with separability and compatibility for these systems.…”
Section: Classicalitymentioning
confidence: 99%
“…the quantum axioms are violated. 15,16 This also sheds new light on the claims of EPR, namely that quantum mechanics is incomplete. This is true, but in a slightly different way: if separated quantum systems do exist, then the corresponding compound system cannot be described by quantum mechanics.…”
Section: When Quantum Axioms Break Down I: Separated Quantum Entitiesmentioning
confidence: 88%
“…It is important to notice that the result of this theorem points at a failure of standard quantum mechanics, and is not just a characteristic of the axiomatic approach itself. Indeed, one can show that the structure on the set of states and set of properties of a compound system of two separated systems does not fit in Hilbert space, i.e., the quantum axioms are violated [25,26]. This also sheds new light on the claims of EPR, namely that quantum mechanics is incomplete.…”
Section: Two Entangled Qubits 51 Description Of Compound Systemsmentioning
confidence: 99%